Analysis on readability of scientific literacy enrichment book on earth science concept. (March 2020) - Puspaningtyas, A A; Hernani,; Suhandi, A
Abstract: The gap between Earth Science material on PISA and on the textbook used at school, encourages research related to the development of scientific literacy enrichment book on Earth Science concept that can support and complement the school textbook. As the learning material source that are used independently, the developed scientific literacy enrichment book is required to have good quality texts that suit to student's reading level. The purpose of this study was to analyse the readability of science book especially scientific literacy enrichment book on earth science context that developed based on scientific literacy competence on PISA 2015. Method on this research was descriptive quantitative with determining main concept on passage as instrument to collect data and Raygor Graph to analyse book's reading grade level. Passage on instrument were passages without graph, picture, or formula. Data collected included main concept explanation for determining passage readability percentage and difficult words for determining reading level of the passage. Participants that contribute on this research were 7 th grade students at one of junior high school in Cilacap distric in Central Java, Indonesia. Data showed that readability percentage of the passage was 56% and categorized as readable. However, it also concluded that the passages were more suitable for 8 th grade student's reading level. It can still be concluded that even though some texts were more suitable for higher class, the developed book was still readable as an enrichment book.